2019
DOI: 10.1002/vjch.201900108
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds from marine Streptomyces sp.: Structure identification and biological activities

Abstract: The marine Iotrochoto purpurea derived Streptomyces sp. IOPU produced ten diverse bioactive compounds: hexahydro-menaquinone MK-9 (1), borrelidin (2), ferulic acid (3), N-acetylanthranilic acid (4), uracil (5), uridine (6), thymidine (7), sitosteryl-3β-D-glucoside, linoleic acid and methyl linoleate. Structures of the obtained compounds were assigned by NMR and mass spectrometric means. The cytotoxic and antimicrobial activities of the extract were visualized against KB-3-1 and KB-V1 cell lines, and a set of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The soft coral-derived fungus Penicillium has a variety of active metabolites, and Boulis et al identified its chemical structure by fingerprinting, and found that the active metabolite has high antibacterial, anti-yeast, and cytotoxic activities [ 7 ]. Abd-Ellatif et al carried out the structural identification of biologically active compounds of marine Streptomyces by spectrometry and chromatography, and tested their biological activities [ 8 ]. Ma et al optimized the extraction process of diterpenoids from Euphorbia.…”
Section: Introductionmentioning
confidence: 99%
“…The soft coral-derived fungus Penicillium has a variety of active metabolites, and Boulis et al identified its chemical structure by fingerprinting, and found that the active metabolite has high antibacterial, anti-yeast, and cytotoxic activities [ 7 ]. Abd-Ellatif et al carried out the structural identification of biologically active compounds of marine Streptomyces by spectrometry and chromatography, and tested their biological activities [ 8 ]. Ma et al optimized the extraction process of diterpenoids from Euphorbia.…”
Section: Introductionmentioning
confidence: 99%
“…Me myristate was promised to be exploited as a hydrophobic medical carrier [ 58 ]. Me linoleate exhibited cytotoxic antibacterial activities against Bacillus subtilis and Staphylococcus aureus [ 59 , 60 ]. Modern medicine often makes acute respiratory distress syndrome models by injecting oleic acid into rabbits or rats [ 61 ].…”
Section: Other Compoundsmentioning
confidence: 99%
“…The genus Streptomyces accounts for a major fraction of all natural products recovered from actinomycetes to date [3]. Streptomyces were recovered from diverse marine sources including sea sediment, sea water and marine invertebrates such as soft corals, tunicates and sponges [4, 5].…”
Section: Full-textmentioning
confidence: 99%
“…Fatty acid composition (%) of strain RV15 T and the type strains of its closest related species Strains: 1, RV15 T ; 2, Streptomyces caeruleatus GIMN 4.002 T ; 3, Streptomyces shaanxiensis CCNWQ 0031 T ; 4, Streptomyces curacoi JCM 4219 T ; 5, Streptomyces lincolnensis NBRC 13054 T . Data for (2) from Lin et al [38], data for (3) from Zhu et al [9], data for (4) from Klykleong et al [39], data for (5) from Nyugen and Kim [40] obtained exactly under the same conditions. tr, traces; -, not detected.…”
mentioning
confidence: 98%